Dielectric study of the electroclinic effect in the smectic-A phase - VIJ, JAGDISH KUMAR (American Physical Society, 1994)
The dielectric properties of a smectic-A liquid crystal in the presence of a dc bias field are studied in the frequency range 100 Hz?1 MHz. It is shown that near the smectic-A?smectic-C* phase transition the relaxation frequency and dielectric strength of the soft mode have nonlinear bias field dependencies resulting from an electroclinic coupling between the molecular tilt and the polarization. A simple mean field theory is proposed to explain the experimental results
PUBLISHED
Keywords: Condensed matter physics; smectic-A liquid crystal